The Role of The Teacher in Designing Innovative and Creative Social Studies Learning - Meylina Eka Setiawati (Social Studies Conference Proceedings, 2022)
Educational Innovation is a change that is new and different from the last thing. As well as deliberately seeking to increase the ability to achieve specific educational goals. Innovation or renewal can be used as a way or tool that produces new media and systems in the learning process, which are then created according to their use so that they lead to progress. Innovation, whether in learning media or technology, is significant in the educational aspect, in which the teacher plays an important role.